ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE - Adhinda Novia Dewanjaya; Tony Sudirgo (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
Tax avoidance remains a significant issue that may reduce government tax revenues, particularly in the property and real estate sector. This study aims to examine the effects of firm size, leverage, capital intensity, and sales growth on tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The study employs a quantitative approach with a causal research design. Secondary data were obtained from annual reports and audited financial statements of companies selected through purposive sampling. The final sample consisted of 18 companies with 60 observations after the outlier elimination process. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results indicate that firm size has a significant negative effect on tax avoidance, while leverage has a significant positive effect on tax avoidance. In contrast, capital intensity does not significantly affect tax avoidance. Sales growth is found to have a significant negative effect on tax avoidance. These findings suggest that company characteristics and financial structure play important roles in determining tax avoidance practices, while investment in fixed assets does not significantly influence corporate tax avoidance behavior in the property and real estate sector.